A polyurethane material for pultruded frame and its preparation method and application

By using fluorine-containing acrylic-hydroxyacrylic acid copolymer and fluorine-containing polyol in the frame material of the photovoltaic panel, polyurethane materials are prepared by pultrusion technology, which solves the problem of corrosion in the existing materials in the marine environment, and achieves the spray-free coating and good weather resistance and hydrophobic properties of the materials.

CN118108922BActive Publication Date: 2025-03-28SHANGHAI PINCHENG HLDG GRP CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410192517.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-21
Publication Date
2025-03-28
Estimated Expiration
2044-02-21

AI Technical Summary

Technical Problem

Existing photovoltaic panel frame materials are prone to corrosion in marine environments and require spraying of polyurethane paint to improve weather resistance, but this still cannot meet the requirements of long-term outdoor use.

Method used

The fluorine-containing acrylic-hydroxyacrylic acid copolymer is used to combine with fluorine-containing polyols to prepare polyurethane materials through a pultrusion process to achieve spray-free spraying of the materials and have good weather resistance and hydrophobic properties.

Benefits of technology

It realizes the corrosion resistance and salt spray resistance of polyurethane materials in marine environments, and does not require spraying, the material has low surface tension, good hydrophobicity and ultraviolet resistance, extending the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004708491630000011
    Figure BDA0004708491630000011
  • Figure BDA0004708491630000021
    Figure BDA0004708491630000021
Patent Text Reader

Abstract

The present invention relates to a polyurethane material for a pultruded frame and a preparation method and application thereof, wherein the components include aromatic isocyanate, aliphatic isocyanate, polyester polyol, polyether polyol, fluorinated acrylic acid-hydroxy acrylic acid copolymer, fluorinated polyol, reactive diluent, catalyst, water scavenger, flame retardant, filler, and other additives. The polyurethane material for a pultruded frame of the present invention has low surface energy, hydrophobicity, and enhanced UV resistance of the material, and the surface tension γc of the pultruded material is less than 32mN / m, which increases the hydrophobicity and weather resistance of the spray-free material, realizes spray-free and also has good weather resistance and hydrophobicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a polyurethane material for a pultruded frame and a preparation method and application thereof. Background Art

[0002] As a representative of green energy, photovoltaic products have been installed in public buildings, factory spaces, offshore coasts and other areas. However, as auxiliary material frames of photovoltaic panels, they are greatly limited. Due to the high ion content in the air on the ocean surface and the high electrolyte content in seawater, the life of ordinary anodized aluminum and galvanized aluminum is greatly reduced, which does not match the 25-year life of the components. At present, in order to achieve the purpose of salt spray and corrosion resistance, polyurethane pultruded frames suitable for use in marine environments have been developed. The high performance of pultruded materials and the high cohesive energy density of resins not only meet the strength requirements for use on the sea surface, but also greatly improve the corrosion resistance. However, most of the current products are surface sprayed polyurethane coating products to achieve further corrosion resistance, salt spray resistance, and UV resistance.

[0003] CN 113527628 B adds unsaturated acrylate to the pultrusion reactants. After pultrusion, the acrylate greatly improves the weather resistance of the photovoltaic frame. However, the free radical reaction is carried out simultaneously with the pultrusion, which limits the molecular weight of the acrylate. In addition, the end group of the hydroxyl acrylic acid cures faster with isocyanate under the action of a catalyst, which results in uncontrollable overall molecular weight of the acrylate. Therefore, the quality of the outdoor product is poor and the physical properties are greatly reduced in the later stage for a long time.

[0004] WO2013000860A1 controls the phosphorus content of the flame retardant by adding phosphorus-containing diols. In order to make up for the phosphorus content, auxiliary flame retardants such as magnesium hydroxide or aluminum hydroxide are added with substances such as N,N-bis-(2-hydroxyethyl)aminomethanephosphonic acid diethyl ester, ammonium polyphosphate and encapsulated red phosphorus to achieve a higher flame retardant level. However, the hydrolysis resistance of the material is also weakened, so the product life will be greatly reduced. A thicker glass fiber outer layer felt needs to be coated during production, and the product needs to be sprayed with polyurethane paint as a protective layer. The technical problems of existing products are still not solved.

[0005] CN 106903910B and US5492583A patents use online spraying, which has high production efficiency. When the product is just solidified after pultrusion, the surface functional groups are still active, the demand for spraying solvents is greatly reduced, and the difference in weather resistance and two spraying is small. However, the product still needs to be sprayed, and the technical problems of existing products are not solved. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a polyurethane material for a pultruded frame and a preparation method and application thereof. The polyurethane material is spray-free and also has good weather resistance and hydrophobic properties.

[0007] The present invention provides a polyurethane material for a pultruded frame, which comprises the following components in parts by weight:

[0008]

[0009]

[0010] Preferably, the aromatic isocyanate is one or more of isophenyl diisocyanate, HDI trimer, p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4-diphenylmethane diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, tri(4-phenylisocyanate)thiophosphate, and triphenylmethane triisocyanate.

[0011] Preferably, the aliphatic isocyanate is one or more of 1,6-hexamethyl diisocyanate, trimethyl-1,6-hexamethylene diisocyanate and isophorone diisocyanate.

[0012] Preferably, the polyester polyol is one or more of adipic acid polyester diol, aromatic polyester polyol, and polycarbonate diol, and the polyester polyol has a hydroxyl value of 50 to 200 mgKOH / g and a weight average molecular weight of 300 to 1500.

[0013] Preferably, the polyether polyol is one or more of polyether diol, polyether triol, polytetramethylene glycol, polyethylene oxide polyol, polytrimethylene ether glycol, and aromatic polyether polyol, and the polyether polyol has a hydroxyl value of 25 to 550 mgKOH / g and a weight average molecular weight of 400 to 1000.

[0014] The preparation method of the fluorinated acrylic acid-hydroxy acrylic acid copolymer comprises the following steps:

[0015] With dimethyl sulfoxide (DMSO) as solvent and N2 as protective gas, hexafluorobutyl acrylate, perfluorohexylethyl acrylate, hydroxy acrylate and styrene are added into a reaction container in a mass ratio of 10:20:40-50:20-30, benzoyl peroxide solution is titrated, the amount of benzoyl peroxide added is 0.2%-0.5%wt of the total amount of the resin within 30-40 minutes, and the mixture is heated in a water bath at 70-80°C and refluxed for 30-40 minutes to obtain a fluorine-containing acrylic acid-hydroxy acrylic acid copolymer.

[0016] The weight average molecular weight of the fluorine-containing acrylic acid-hydroxy acrylic acid copolymer is controlled between 2000 and 4000, and the hydroxyl value is between 79 and 89 mgKOH / g.

[0017] Preferably, the active diluent is polycaprolactone diol, with a hydroxyl value of less than 300 mgKOH / g and a weight average molecular weight of less than 700.

[0018] Preferably, the fluorine-containing polyol is a fluorine-substituted fatty ether diol, and the fluorine content is 40-60 wt%.

[0019] Preferably, the catalyst is one or more of lead octoate, stannous octoate, dibutyltin dilaurate, cobalt octoate, iron octoate, zinc naphthenate, tetraisobutyl titanate, and triethylenediamine.

[0020] Preferably, the dehydrating agent is one or more of an oxazolidine dehydrating agent, a carbodiimide dehydrating agent, an orthoformate triester dehydrating agent, and p-toluenesulfonyl isocyanate.

[0021] Preferably, the filler is one or more of fumed silica, carbon black, and carbon nanotubes.

[0022] Preferably, the flame retardant is a bromine-containing or chlorine-containing polyether polyol with a functionality of 2 to 3 and a bromine content higher than 30%.

[0023] Preferably, the other additives include, by weight, 0.5-1 parts of defoaming agent; 0.1-0.3 parts of release agent; 0.1-0.3 parts of antioxidant; 0.1-0.3 parts of UV absorber; and 0.1-0.3 parts of light stabilizer.

[0024] Furthermore, the defoaming agent is a silicone defoaming agent.

[0025] Furthermore, the release agent is AXEL release agent.

[0026] Furthermore, the antioxidant includes antioxidant 1010, antioxidant 168 and the like.

[0027] Furthermore, the UV absorber is UV234 or the like.

[0028] Furthermore, the light stabilizer is UV1164 or the like.

[0029] The present invention also provides a method for preparing a polyurethane material for a pultruded frame, comprising the following steps:

[0030] (1) mixing aromatic isocyanate, aliphatic isocyanate and fluorinated acrylic acid-hydroxy acrylic acid copolymer according to a ratio to form raw material A;

[0031] (2) Proportioning: polyester polyol, polyether polyol and fluorine-containing polyol are mixed, water is removed, other components are added after cooling, and stirred evenly to obtain raw material B;

[0032] (3) Mixing raw material A and raw material B to obtain a polyurethane material for a pultruded frame.

[0033] The invention also provides an application of the polyurethane material for pultruded frame in photovoltaic products.

[0034] Preferably, the application steps are: injecting the polyurethane material for the pultruded frame into the glue injection box, driving the fibers or fiber fabrics through the yarn frame and the yarn guide plate to form strands under the drive of the traction machine, and then passing through the glue injection box at a predetermined speed. The mold temperature is three-stage temperature control, the head is 35-120°C, the gel zone is heated to 150°C, and the continuous fibers impregnated with resin are 80% cured before passing through the mold; after pultrusion, they are treated at 120°C for 20 minutes to achieve a further cross-linking effect.

[0035] Beneficial Effects

[0036] (1) The fluorine-containing group component in the polyurethane material for the pultruded frame of the present invention will be partially exposed on the surface of the frame after pultrusion, and has low surface energy, hydrophobicity, and enhanced UV resistance of the material. The surface tension γc of the pultruded material is less than 32mN / m, which increases the hydrophobicity and weather resistance of the spray-free material, achieving spray-free while also having good weather resistance and hydrophobicity.

[0037] (2) The present invention adopts a fluorinated acrylic acid-hydroxy acrylic acid copolymer, and the acrylic acid ester units are evenly distributed during pultrusion, which can overcome the low molecular weight caused by random copolymerization and the reduced performance caused by the residual initiator. Therefore, the spray-free frame can be directly exposed to the sun.

[0038] (3) The present invention uses a fluorinated acrylic acid-hydroxy acrylic acid copolymer and a fluorinated polyol to further optimize the light aging resistance of the polyurethane.

[0039] (4) The present invention increases the carbon content by adding aromatic isocyanate and forms a composite system with the flame retardant to achieve the UL94 thinnest 1.6mmV-1 flame retardancy rating.

[0040] (5) The present invention reduces the viscosity increased by high molecular weight acrylic acid by adding a reactive diluent, making the material easier to extrude. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0042] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0043] The fluorinated acrylic acid-hydroxy acrylic acid copolymer is prepared by the following process:

[0044] With dimethyl sulfoxide (DMSO) as solvent and N2 as protective gas, hexafluorobutyl acrylate, perfluorohexylethyl acrylate, hydroxy acrylate and styrene are added into a reaction container, and benzoyl peroxide solution (10 g / L, solvent is DMSO) is titrated, the amount of benzoyl peroxide added is 0.2% to 0.5% by weight of the total amount of the resin within 30 minutes, and the mixture is heated in a water bath at 75°C and refluxed for 30 minutes to obtain a fluorinated acrylic acid-hydroxy acrylic acid copolymer.

[0045] The raw material ratio of fluorinated acrylic acid-hydroxy acrylic acid copolymer is as follows:

[0046]

[0047] The polyurethane material for pultruded frames of each embodiment and comparative example is prepared by the following process:

[0048] (1) mixing aromatic isocyanate, aliphatic isocyanate and fluorinated acrylic acid-hydroxy acrylic acid copolymer according to a ratio to form raw material A;

[0049] (2) Proportioning: polyester polyol, polyether polyol and fluorine-containing polyol are mixed, dehydrated at 120° C. for 1 h, and then other components are added after cooling and stirred evenly to obtain raw material B;

[0050] (3) Mixing raw material A and raw material B to obtain a polyurethane material for a pultruded frame.

[0051] Application of photovoltaic products:

[0052] The polyurethane material for the pultruded frame is injected into the glue injection box, and the fibers or fiber fabrics are gathered into strands through the yarn frame and the yarn guide plate under the drive of the traction machine, and then pass through the glue injection box at a predetermined speed. The mold temperature is three-stage temperature control, the head is 120°C, and the gel zone is heated to 150°C. The continuous fiber impregnated with resin completes 80% of curing before passing through the mold; after pultrusion, it is treated at 120°C for 20 minutes to achieve a further cross-linking effect.

[0053] The raw materials used in the following examples and comparative examples are as follows:

[0054]

[0055]

[0056] The raw material ratios used in the following examples and comparative examples are as follows:

[0057]

[0058] The product test results of the following embodiments and comparative examples are as follows:

[0059]

[0060] It can be seen from the above results that the material of the present invention not only achieves spray-free but also has good weather resistance and hydrophobicity, among which the addition of fluorinated acrylic acid-hydroxy acrylic acid copolymer and fluorinated polyol is particularly critical.

Claims

1. A polyurethane material for a pultruded frame, characterized in that: In parts by weight, it comprises the following components: Diol.

2. The polyurethane material for pultruded frame according to claim 1, characterized in that: The aromatic isocyanate is one or more of isophenyl diisocyanate, HDI trimer, p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4-diphenylmethane diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, tri(4-phenylisocyanate)thiophosphate, and triphenylmethane triisocyanate; the aliphatic isocyanate is one or more of 1,6-hexamethyl diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, and isophorone diisocyanate.

3. The polyurethane material for pultruded frame according to claim 1, characterized in that: The polyester polyol is one or more of adipic acid polyester diol, aromatic polyester polyol, and polycarbonate diol, the hydroxyl value of the polyester polyol is 50-200 mgKOH / g, and the weight average molecular weight is 300-1500; the polyether polyol is one or more of polyether diol, polyether triol, polytetrahydrofuran diol, polyethylene oxide polyol, polytrimethylene ether diol, and aromatic polyether polyol, the hydroxyl value of the polyether polyol is 25-550 mgKOH / g, and the weight average molecular weight is 400-1000.

4. The polyurethane material for pultruded frame according to claim 1, characterized in that: The preparation method of the fluorinated acrylic acid-hydroxy acrylic acid copolymer comprises the following steps: With dimethyl sulfoxide (DMSO) as solvent and N2 as protective gas, hexafluorobutyl acrylate, perfluorohexylethyl acrylate, hydroxy acrylate and styrene are added into a reaction container in a mass ratio of 10:20:40-50:20-30, benzoyl peroxide solution is titrated, the amount of benzoyl peroxide added is 0.2%-0.5%wt of the total amount of the resin within 30-40 minutes, and the mixture is heated in a water bath at 70-80°C and refluxed for 30-40 minutes to obtain a fluorine-containing acrylic acid-hydroxy acrylic acid copolymer.

5. The polyurethane material for pultruded frame according to claim 1, characterized in that: The active diluent is polycaprolactone diol, the hydroxyl value of which is below 300 mgKOH / g and the weight average molecular weight of which is below 700.

6. The polyurethane material for pultruded frame according to claim 1, characterized in that: The catalyst is one or more of lead octoate, stannous octoate, dibutyltin dilaurate, cobalt octoate, iron octoate, zinc cyclohexaneate, tetraisobutyl titanate, and triethylenediamine; the dehydrating agent is one or more of oxazolidine dehydrating agent, carbodiimide dehydrating agent, triester orthoformate dehydrating agent, and p-toluenesulfonyl isocyanate.

7. The polyurethane material for pultruded frame according to claim 1, characterized in that: The filler is one or more of fumed silica, carbon black and carbon nanotubes; the flame retardant is bromine-containing or chlorine-containing polyether polyol.

8. The polyurethane material for pultruded frame according to claim 1, characterized in that: The other additives include, by weight, 0.5-1 part of a defoamer; 0.1-0.3 part of a release agent; 0.1-0.3 part of an antioxidant; 0.1-0.3 part of a UV absorber; and 0.1-0.3 part of a light stabilizer.

9. A method for preparing the polyurethane material for pultruded frame according to claim 1, comprising the following steps: (1) mixing aromatic isocyanate, aliphatic isocyanate and fluorinated acrylic acid-hydroxy acrylic acid copolymer according to a ratio to form raw material A; (2) Proportioning: polyester polyol, polyether polyol and fluorine-containing polyol are mixed, water is removed, other components are added after cooling, and stirred evenly to obtain raw material B; (3) Mixing raw material A and raw material B to obtain a polyurethane material for a pultruded frame.

10. Use of the polyurethane material for pultruded frame according to claim 1 in photovoltaic products.

Citation Information

Patent Citations

  • Coating methods for polyurethane pultruded composite materials

    CN106903910B

  • A thermosetting polyurethane acrylic resin and its application

    CN113527628B

  • Apparatus and method for in-line coating of pultrusion profiles

    US5492583A

  • Flame resistant composition, fiber reinforced polyurethane based composite article comprising the flame resistant composition and its use

    WO2013000860A1

  • Fluorine-containing acrylic acid modified polyurethane wear-resistant resin and preparation method thereof

    CN114249872A